Juridical Analysis of Mandatory Vaccination Implementation During a Pandemic - N.Barasa; O.Cahyono (International Medical Journal Corp. Ltd, 2024)
Introduction The implementation of mandatory vaccination during a public health crisis represents a profound legal and ethical dilemma, balancing collective biosecurity against individual autonomy. This study addresses the constitutional friction arising from state-enforced medical interventions designed to curb highly contagious diseases. Methods Using a normative juridical research method, this study analyzes statutory frameworks, constitutional provisions, and human rights instruments to evaluate the state's authority in enforcing public health mandates. Results The statutory analysis reveals that while constitutional frameworks guarantee the right to health and bodily integrity, they concurrently empower the state to restrict individual liberties during declared emergencies to preserve public order and safety. The judiciary consistently upholds public health mandates, provided they satisfy the principles of legality, necessity, and proportionality. Discussion The legal discourse centers on the doctrine of salus populi suprema lex esto, which establishes public welfare as the highest law. However, a significant research gap exists regarding the precise legal thresholds required to transition from voluntary recommendations to coercive mandates without committing constitutional overreach. This paper fills that gap by establishing a novel, structured three-tiered juridical framework—assessing scientific certainty, systemic healthcare capacity, and the availability of less restrictive alternatives—to determine the constitutional legitimacy of mandatory vaccination policies. Conclusions Mandatory vaccination is legally justifiable under international and domestic law when voluntary compliance fails to achieve herd immunity during a severe pandemic. Governments must ensure clear legislative authorization, non-discriminatory enforcement, and robust compensation frameworks for rare adverse events to maintain public trust and constitutional validity.